Research of the Crank-group Driving Mechanism based on Topology Theory - Wang Yuqi; Cao Jujiang; Luo Jie (Jixie chuandong)
Based on the topologic theory,the topology structure of the crank-group driving mechanism is researched,and the similarities and differences of the crank-group driving mechanism structure between them are determined by combining with the topology structure matrix. It has a certain referential significance for the further research of the crank-group driving mechanism.